Reinfection, immunity and prevention of transmission of COVID-19 - Humberto Guanche Garcell; Reynaldo Barbán Arias (Universidad de Ciencias Médicas de La Habana, 2021)
Introduction: The duration of natural immunity generated by COVID-19 is yet to be defined, which determines the probable reinfection. Objective: To analyze issues related to natural infection and the need to maintain prevention practices regarding a case of reinfection in a health care worker. Case presentation: Forty-eight-year-old female patient without comorbidities who was diagnosed with COVID-19 in June 2020 and March 2021, in both cases as a mild symptomatic disease. Twenty-four hours after the onset with headache, dizziness, and dry cough, the diagnosis of SARS CoV-2 infection was confirmed by positive PCR and cycle threshold (CT) at 24.84. Nine months and nine days after original infection, and two days after receiving the BNT162b2 vaccine (Pfizer-BioNTech), the patient began with general malaise, dry cough, runny nose, and sore throat, with a positive PCR and CT of 17.61. Conclusions: The possibility of reinfection by COVID-19 points to the need to strengthen transmission prevention practices in healthcare facilities as long as scientific evidence provides us with more effective resources for its control.